Study on Effect of Infill Density to 3D Printed Part by Using Chi Mei Polylac® PA-757 ABS Filament - Muhammad ‘Ariff Zakaria Ahmad Nizar; Kamarudin, Khairu (Progress in Engineering Application and Technology, 2022)
In additive manufacturing, it is very important to ascertain the suitability of material used in the process, especially fused filament fabrication (FFF) as poor selection of material will severely affect the printer part mechanical properties. This paper aims to determine the compatibility of Chi Mei Polylac® PA-757 ABS pellet with FFF printer which was initially made for injection moulding purposes. The ABS pellet was extruded into filaments using Wellzoom desktop filament extruder B and used to print test sample using Ultimaker 2+ with different infill densities, which then put into tensile and Izod (notched) impact test with ASTM D638 and ASTM D256 standard respectively. Tensile properties and impact resistance of printed sample was compared with previous work and pellet mechanical properties. Through FFF process, samples printed using Chi Mei Polylac® PA-757 ABS pellet lost around 9-19% of its tensile properties and nearly 25% of its impact resistance. Tensile properties increase linearly as infill density increases, while impact resistance increase exponentially as infill density increases. Further improvement in future research to Chi Mei Polylac® PA-757 ABS pellet mechanical properties is highly suggested by either combining with other polymer or mixing with additive material.